Effect of pilates method on inspiratory and expiratory muscle strength in the elderly - Tozim, Beatriz Mendes [UNESP]; Navega, Marcelo Tavella [UNESP] (Universidade Federal de Santa Catarina, 2018)
With aging, the respiratory muscle strength decreases and the Pilates method is a technique that uses respiration as one of its principles. The present study has the aim of analyzing the influence of the Pilates method on respiratory muscle strength in older women. For the evaluation of respiratory muscle strength (inspiratory and expiratory), manovacuometer was used. Thirty-oneolder women were divided into two groups: 14 participated in the Pilates group and 17 in the control group. Participantsof the Pilates group performed 16 sessions of Pilates method with an hour of training, twice week for eight weeks. The control group participated in four educational lectures for eight weeks. For statistical analysis, Shapiro-Wilk, ANOVA for repeated measures (p <0.05) and Cohen’s D index were performed. The results showed significant difference and the mean effect for the Cohen’s D index expiratory muscle strength of the Pilates group when comparing before (69.71 ± 25.48) and after (85.23 ± 22.21) training (p<0.05) with an increase of 23%. The results of inspiratory muscle strength were not significant but presented an average effect for the Cohen’s D index for the Pilates group before (69.71 ± 35.46) and after (88.00 ± 34.87) training, with an increase of 27%. The control group did not present significant differences for the variables evaluated. It could be concluded that the Pilates method is effective in improving expiratory muscle strength and provides positive effects on the increase in inspiratory muscle strength.

Com o envelhecimento, a força muscular respiratória diminui e o método Pilates é uma técnica que utiliza da respiração como um de seus princípios. Com isso, o presente estudo tem como objetivo analisar a influência do método Pilates na força muscular respiratória em idosas. Para a avaliação da força dos músculos respiratórios (inspiratórios e expiratórios) foi utilizado o manovacuomêtro. Participaram da pesquisa 31 idosas que foram divididas em dois grupos, 14 idosas participaram do grupo Pilates e 17 do grupo controle. As idosas participantes do grupo Pilates realizaram 16 sessões com uma hora de treinamento, duas vezes na semana, durante oito semanas. Quanto ao grupo controle, as idosas participaram de quatro palestras educativas durante oito semanas. Para a análise estatística foi realizado o teste de Shapiro-Wilk, ANOVA para medidas repetidas e o D de Cohen. Os resultados mostraram diferença significativa e efeito médio para o índice de D de Cohen da força dos músculos expiratórios do grupo Pilates, ao comparar antes (69,71 ± 25,48) e após (85,23 ± 22,21) o treinamento (p<0,05), com aumento de 23%. Os resultados da força muscular inspiratória não apresentaram diferença significativa, mas apresentou efeito médio para o índice de D de Cohen para o grupo Pilates comparando antes (69,71 ± 35,46) e após (88,00 ± 34,87) o treinamento, com um aumento de 27%. O grupo controle não apresentou diferença significativa para as variáveis avaliadas. Pode-se concluir que o método Pilates é eficaz na melhora da força muscular expiratória e apresenta efeito positivo sobre o aumento da força muscular inspiratória.
Efeito do método pilates na força dos músculos inspiratórios e expiratórios em idosos
Keywords: Muscle strength; Physical therapy modalities; Respiratory function tests; Força muscular; Modalidades de fisioterapia; Testes de função respiratória